Indigenization of Islam and Local Culture in Manuscript of the Wawacan Nabi Medal - Fenty Sukmawaty; Eva Syarivah Wardah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
As one of the regions with a long history of cultural and religious interaction, the Sundanese people have developed a distinctive literacy tradition in accommodating the influence of Islam. Local texts produced during the Islamization period reflect the creative ways in which communities contextualized new teachings within their cultural worldview. This study examines the Wawacan Nabi Medal (WNM) manuscript as a significant expression of the indigenization of Islam in the Sundanese region. Written in Sundanese and structured in pupuh, the text narrates the life cycle of the Prophet Muhammad while integrating local cultural elements such as language, social values, religious practices, and artistic forms familiar to Sundanese audiences. The research employs a descriptive qualitative approach using philological and sociocultural methods to understand how Islamic teachings were adapted through the wawacan tradition. The primary source is the WNM manuscript from the collection of Muhammad Supyandi in Jampang Kulon, written in Pegon and containing several pupuh. Data were collected through manuscript inventory, transliteration, and content analysis to identify cultural expressions and Islamic values within the text. The philological work applies the standard manuscript method, using the Supyandi copy as the base manuscript due to its completeness and textual stability, supported by diplomatic transcription, limited normalization, and documentation of significant variants in a critical apparatus. The findings show that WNM represents a harmonious synthesis between Islamic teachings and Sundanese cultural identity. The prophetic narrative is reshaped into poetic form and endowed with ritual meaning, allowing Islam to be internalized not as an external force but as a tradition deeply rooted in local sensibilities. Through this process, WNM stands as a clear example of the successful indigenization of Islam in the cultural landscape of the archipelago.